2018
DOI: 10.1111/1750-3841.14096
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Temporal Dominance of Sensation (TDS) and Quantitative Descriptive Analysis (QDA™) to Identify Flavors in Strawberries

Abstract: A comparison of TDS to traditional descriptive analysis indicate that TDS provides additional information to QDA™ regarding the lingering component of eating. The QDA™ results however provide more precise detail regarding singular attributes. Therefore, the TDS methodology has an application in industry when it is important to understand the lingering profile of products. However, this methodology should not be employed as a replacement to traditional descriptive analysis methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
(71 reference statements)
1
15
0
5
Order By: Relevance
“…[7,8] QDA is not only a flavor inspection method with the function of analysis, description and quantification, but also a practical quality evaluation tool. [9][10][11] This method has also been gradually applied to the field of tea sensory evaluation. The descriptors of green tea infusion taste, [12] green tea aroma, [13] black tea aroma, [14] and Dianhong flavor [15] have been achieved, respectively, and their intensity to obtain the flavor characteristics of related tea categories and improve people's sensory awareness of the quality of tea leaves were evaluated by QDA.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] QDA is not only a flavor inspection method with the function of analysis, description and quantification, but also a practical quality evaluation tool. [9][10][11] This method has also been gradually applied to the field of tea sensory evaluation. The descriptors of green tea infusion taste, [12] green tea aroma, [13] black tea aroma, [14] and Dianhong flavor [15] have been achieved, respectively, and their intensity to obtain the flavor characteristics of related tea categories and improve people's sensory awareness of the quality of tea leaves were evaluated by QDA.…”
Section: Introductionmentioning
confidence: 99%
“…The TDS method has been used in tandem with static sensory profiling to evaluate different types of products, making it possible to identify sensory characteristics that are not picked up by one method alone. For example, this combined approach has proven to be useful for studying the persistence of gel containing odorants [ 26 ]; interactions between texture and aroma in model candies [ 27 ]; solid foods with contrasting textural layers (i.e., fish sticks) [ 28 ]; interactions between olive oil composition and pureed beans and tomatoes [ 29 ]; the influence of aroma on taste and texture in an apple matrix [ 30 ]; and the key flavors perceived in strawberries [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Flash profiling is a commonly used method and its ability to differentiate products based on panelist‐generated profiles in combination with product ranking has been widely studied (Albert, Varela, Salvador, Hough, & Fiszman, 2011; Delarue & Sieffermann, 2004; He & Chung, 2019; Liu, Bredie, Sherman, Harbertson, & Heymann, 2018). Another frequently studied rapid methodology is Temporal Dominance of Sensations, or TDS (Albert, Salvador, Schlich, & Fiszman, 2012; Labbe, Schlich, Pineau, Gilbert, & Martin, 2009; Oliver, Cicerale, Pang, & Keast, 2018; Pineau et al, 2012). TDS involves having assessors identify and quantify dominant sensations as they appear throughout the evaluation of a product.…”
Section: Introductionmentioning
confidence: 99%
“…While recent studies have found that flash profiling and TDS procedures provide similar profiles to traditional descriptive methods (He & Chung, 2019; Oliver et al, 2018), these alternative methods still present limitations. Flash profiling allows assessors to develop their own individual attribute lists, so the sample descriptions can vary widely and be difficult to interpret (Varela & Ares, 2012).…”
Section: Introductionmentioning
confidence: 99%